Exploitation of mitochondrial nad6 as a complementary marker for studying population variability in Lepidoptera - Silva-Brandão, Karina L.; Lyra, Mariana L. [UNESP]; Santos, Thiago V.; Seraphim, Noemy; Albernaz, Karina C.; Pavinato, Vitor A.C.; Martinelli, Samuel; Cônsoli, Fernando L.; Omoto, Celso (Sociedade Brasileira de Genética, 2011)
The applicability of mitochondrial nad6 sequences to studies of DNA and population variability in Lepidoptera was tested in four species of economically important moths and one of wild butterflies. The genetic information so obtained was compared to that of cox1 sequences for two species of Lepidoptera. nad6 primers appropriately amplified all the tested DNA targets, the generated data proving to be as informative and suitable in recovering population structures as that of cox1. The proposal is that, to obtain more robust results, this mitochondrial region can be complementarily used with other molecular sequences in studies of low level phylogeny and population genetics in Lepidoptera.
Keywords: cytochrome c oxidase I; Diatraea saccharalis; DNA polymorphism; Hermeuptychia atalanta; Noctuidae